Prospect for lectins in arthropods - Viswambari Devi, R.; Basilrose, M. R.; Mercy, P. D. (The Italian journal of zoology, 2010)
Invertebrates lack an adaptive immune system, but have developed efficient innate immune systems to defend themselves against foreign materials. Molecular structures and functions of various defense components that participate in immune processes are being discovered. New molecules such as fibrinogen-related proteins (FREPs) are being uncovered that might have the potential to recognize and attack specific pathogens, while the roles of better-studied molecules continue to expand. This challenges the idea that invertebrates are adequately served by broad-spectrum pathogen recognition proteins. Lectins are one such protein that is involved in defense and various biological phenomena. Their role in arthropods is discussed. Lectins may recognize a part of a sugar, a whole sugar, their glycosidic linkages or a sequence of sugars. This property of lectins has moved their efficacy to humans in various biological applications, which are also discussed.